Gibbs excess energy model to predict phase behaviour of brine/oil/surfactant mixtures for Chemical Enhanced Oil Recovery CEOR methods - Adeeyo, Y.A. (Society of Petroleum Engineers, 2016)
With the increase in the world population, increases in scientific and industrial activities have engendered spontaneous upsurge in the global demand for oil and gas in the past few years. These resulted in depletion of major world oil reservoir without corresponding discovery of new major oil fields. However, substantial amount of oil is trapped inside the reservoir. This oil is being held by capillary force which depends on interfacial tension (IFT) between oil and water. Therefore, reducing the IFT releases the oil and enables greater recovery. Surfactant (surface acting agent) reduces IFT and has been tested to be appropriate for use under reservoir condition. A mixture of surfactant, brine and oil may produce microemulsion depending on the proportion of the amount of the components and thermodynamic parameters involved. Microemulsion reduces IFT. The practice in the industry is to conduct laboratory experiments to investigate various formulations and identify the thermodynamic conditions that will yield microemulsion phase. This study is aimed at developing mathematical thermodynamic model and computation algorithm using excess Gibbs energy, fugacity and group contribution model (GCM) for the estimation of critical properties of the pseudo-components to predict phase behavior of water/oil surfactant mixture in the regions and beyond those their measurements have been conducted in the lab. The model was validated by comparing its performance to lab results. The lab experiments involved measuring the phase behaviour of the mixture of Alfa Olefin Sulfonate (AOS) surfactant, decane and brine. The model shows good performance and will be useful in the prediction of phase behavior of water/oil surfactant and can be used in compositional simulation of surfactant flooding operations and should be an invaluable tool in planning and evaluation of surfactant flooding processes. Copyright 2016, Society of Petroleum Engineers.